2020
DOI: 10.3390/ijms21165832
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Drug Release and Cytotoxicity Studies of Beta-Lapachone and Doxorubicin Loaded into Cyclodextrins Attached to a Polyethyleneimine Matrix

Abstract: This work presents a new look at the application of cyclodextrins (CD) as a drug nanocarrier. Two different cyclodextrins (αCD, βCD) were covalently conjugated to branched polyethylenimine (PEI), which was additionally functionalized with folic acid (PEI-βCD-αCD-FA). Here, we demonstrated that the combination of αCD and βCD enabled to load and control release of two anticancer drugs: doxorubicin (DOX) and beta-lapachone (beta-LP) (DOX in β-CD and beta-LP into α-CD) via host-guest inclusion. The PEI-βCD(DOX)-αC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…There are special phenomena such as color changes in the merging processes and the particularity of red-shift and bonding formations. When added DOX, the color changed from orange-red to blue-purple, and the UV absorption peak of the Au-Ag cluster @PEI-DOX shifted from 480 nm to 580 nm, which was due to the formation of hydrogen bond between the carbonyl group of DOX (as hydrogen acceptor) and the -NH 2 group of PEI (hydrogen donor) [ 60 ]. Amino groups interacted rapidly with the carbonyl groups on DOX to form hydrogen bonds in aqueous solution, and its morphological features can be seen in the TEM images as a striated structure with the appearance of a lattice ( Figure S5b,c ).…”
Section: Resultsmentioning
confidence: 99%
“…There are special phenomena such as color changes in the merging processes and the particularity of red-shift and bonding formations. When added DOX, the color changed from orange-red to blue-purple, and the UV absorption peak of the Au-Ag cluster @PEI-DOX shifted from 480 nm to 580 nm, which was due to the formation of hydrogen bond between the carbonyl group of DOX (as hydrogen acceptor) and the -NH 2 group of PEI (hydrogen donor) [ 60 ]. Amino groups interacted rapidly with the carbonyl groups on DOX to form hydrogen bonds in aqueous solution, and its morphological features can be seen in the TEM images as a striated structure with the appearance of a lattice ( Figure S5b,c ).…”
Section: Resultsmentioning
confidence: 99%
“…A diverse number of carriers of chemotherapy agents have been reported that have pH-sensitive non-covalent interactions. These non-covalent bonds have been found between chemotherapy agents and carriers, including DNA, cyclodextrin, and carbon dots [ 97 , 98 , 99 , 100 ]. These bonds are primarily ionic but include supporting roles from hydrogen and hydrophobic bonds [ 101 ].…”
Section: Ph-sensitive Bondsmentioning
confidence: 99%
“…Hydroxyl groups of CyDs that aligned on the surface of truncated cone are important in grafting with other functional molecules. The CyDs were modified by several typical chemical reactions (such as amination, halogenation, esterification, and sulfonation) and introduce amine, halogen, alkoxy and sulfite groups that can be further modified or self-assembled [6,92,102]. Therefore, the intrinsic ability of CyD allows the synthesis of a series of self-assembled supramolecular structures with different functions via noncovalent interactions.…”
Section: Self-assemble Capabilitymentioning
confidence: 99%
“…However, the amphiphilic part could interact with both surrounding solution molecule and hydrophobic part. A very extensively studied self-assembly process is the self-assembly of block or graft copolymers, where incompatible polymer chains are bonded covalently [102]. This part can be systematically acknowledged from elsewhere [2,31,103,104].…”
Section: Self-assembly Directed By Hydrophilic-hydrophobic Interactionsmentioning
confidence: 99%